'Best available science' approach to management decisions by the Commission for the Convention on the Conservation of Antarctic Living Resources: consistent or selective?. Issue 1 (2nd January 2022) - Goldsworthy, L.D.
ABSTRACT: The Convention on the Conservation of Antarctic Marine Living Resources is responsible for managing human activities in the Southern Ocean. The Convention's Commission meets annually to determine management decisions to deliver the Convention's objective of conservation of Antarctic marine living resources (including rational use). Members are required to base these decisions on the 'best available scientific advice', meaning the best scientific information available at the time. Applied correctly this approach is an effective way to implement the precautionary approach required by the Convention. This paper reviews the Commission's responses to the Scientific Committee's recommendations, to assess the extent to which it has used best available scientific information in its decision making. It concludes that since 1990, there has been a consistently high uptake of 'best available science' by the Commission, particularly for general fisheries regulation and specific finfish fisheries, and that progress is steady on the implementation of long-term krill management. However, there are inconsistencies in the approach to the application of 'best available science' for issues that extend outside explicit fisheries management. Without embracing its obligation to consistently use best available science across all management and conservation responsibilities, the Commission will face challenges in effectively delivering the Convention's objective.